Autism Rating Scale: A New Tool for Characterizing the Schizophrenia Phenotype - Palumbo, Davide; Stanghellini, Giovanni; Mucci, Armida; Ballerini, Massimo; Giordano, Giulia Maria; Lysaker, Paul H.; Galderisi, Silvana (Frontiers in Psychiatry, 2021)
Social dysfunctions (SD) are frequently observed in subjects with schizophrenia. Some of these dysfunctions are also observed in other neuropsychiatric disorders such as autism spectrum disorders (ASD), major depression, bipolar disorder or Alzheimer disease. Recently, a characterization of a specific type of SD in schizophrenia has been proposed, with the concept of dis-sociality, which form the core aspect of “Schizophrenic Autism” (SA). The present study aimed to explore the presence in people with schizophrenia of SA, independent of other autistic traits, which can be often found in schizophrenia and other neurodevelopmental disorders. We used a structured interview - the Autism Rating Scale (ARS), an instrument devised to detect and measure SA. Fifty-one outpatients affected by schizophrenia (26 remitted, SCZ-r) and 28 affected by bipolar disorder type 1, with psychotic features, in the euthymic phase (BD-e) were recruited. Before assessing the specificity for schizophrenia of SA, we tested the internal consistency, the convergent and divergent validity of the ARS in the schizophrenia sample. Specificity was assessed by examining potential differences in ARS scores between SCZ-r and BD-e subjects. ARS showed good internal consistency, as well as convergent and divergent validity. ARS items were more frequently of moderate severity in SCZ-r than in BD-e subjects. This scale can contribute to establish more precise phenomenal boundaries between schizophrenia, ASD and bipolar disorder, as well as to characterize different types of SD in schizophrenia, which might benefit of different treatments.